ATB-LMTO approach to study structural stability and electronic behavior of transition metal dichalcogenides MX2 (M=Zr,HfANDX=S,Se) - Chaudhary, Saroj Kumar; Kaphle, Gopi Chandra (Himalayan Physics, 2019)
Available with fulltext.